Nicaragua propuesta para la reforma del sistema de pensiones - D´Ferranti, D.; Dowsett-Coirolo, D.; Leipziger, D. M.; Navarro, M. (Washington (EUA), 2000)
Sumario (Es)
Ilus., 26 ref.
Keywords: SEGURIDAD SOCIAL; SERVICIOS SOCIALES; ORGANIZACION SOCIOECONOMICA; JUBILACIONES; SALUD PUBLICA; NICARAGUA